2015
DOI: 10.1016/j.eururo.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrated Human Amnion/Chorion Membrane Allograft Nerve Wrap Around the Prostatic Neurovascular Bundle Accelerates Early Return to Continence and Potency Following Robot-assisted Radical Prostatectomy: Propensity Score–matched Analysis

Abstract: We present a propensity-matched analysis of patients undergoing placement of dehydrated human amnion/chorion membrane (dHACM) around the neurovascular bundle (NVB) during nerve-sparing (NS) robot-assisted laparoscopic prostatectomy (RARP). From March 2013 to July 2014, 58 patients who were preoperatively potent (Sexual Health Inventory for Men [SHIM] score >19) and continent (no pads) underwent full NS RARP. Postoperative outcomes were analyzed between propensity-matched graft and no-graft groups, including ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 10 publications
0
65
0
Order By: Relevance
“…Patel et al [50] used a dehydrated human amnion/chorion membrane (dHACM) placed around the NVBs and studies its impact on return of erectile function and UC. In a prospective propensity-matched cohort study in 58 men undergoing RARP, they were able to show that UC at 8 weeks returned in 81.0% of the dHACM group and 74.1% of the no-dHACM group ( p  = 0.373).…”
Section: Surgical Techniques To Optimize Urinary Continencementioning
confidence: 99%
“…Patel et al [50] used a dehydrated human amnion/chorion membrane (dHACM) placed around the NVBs and studies its impact on return of erectile function and UC. In a prospective propensity-matched cohort study in 58 men undergoing RARP, they were able to show that UC at 8 weeks returned in 81.0% of the dHACM group and 74.1% of the no-dHACM group ( p  = 0.373).…”
Section: Surgical Techniques To Optimize Urinary Continencementioning
confidence: 99%
“…In another study, it was effective following nerve‐sparing robot‐assisted radical prostatectomy, when it was placed around the prostatic neurovascular bundle. In patients who received amniotic transplants, the recovery of urinary continence and potency was faster than in control group, with no adverse effect of the therapy . Interestingly, the usefulness of amniotic membrane in regenerative periapical endodontic surgery was shown when it was combined with bone graft and platelet‐rich fibrin (PRF).…”
Section: New and Unusual Applications Of Amniotic Membrane In The Woumentioning
confidence: 99%
“…In patients who received amniotic transplants, the recovery of urinary continence and potency was faster than in control group, with no adverse effect of the therapy. 108 Interestingly, the usefulness of amniotic membrane in regenerative periapical endodontic surgery was shown when it was combined with bone graft and platelet-rich fibrin (PRF). Such combination enhanced the radiographic healing outcome and decreased post-operative discomfort in patients suffering from radicular cysts.…”
Section: New and Unusual Applications Of Amniotic Membrane In The Wmentioning
confidence: 99%
“…Patel et al [53] reported the first study about preoperatively potent 58 cases who had bilateral nerve-sparing RARP by the application of dehydrated human amniotic membrane as the wrap on NVB. In short term results, the potency and the continence rates were found significantly higher than the other group.…”
Section: Nerve-sparing Surgical Techniques In Rarpmentioning
confidence: 99%